The Concept of Happiness in Max Frei’s Novel The Key of Yellow Metal: Hamlet and Siddhartha - Kanchura, Yevheniia (Literatūra, 2024)
This article explores the motif of an ‘(un)happy prince’ as it is manifested through the evocation of Hamlet’s and Siddhartha’s imagery within Max Frei’s novel The Key of Yellow Metal (2009). The research offers an in-depth analysis of the functioning of these references within the broader intertextual landscape of the novel, placed within the Vilnius narrative. The theme of the happy prince’s perception of human suffering is entwined with the topoi of hell and paradise, as well as home or lost paradise. Traditional imagery plays a pivotal role in shaping the concept of inspiration and madness as dynamic forces that exert a profound influence on the surrounding world, counterbalancing the notion of eternal suffering. The shift of focalization allows us to reconsider Sartre’s idea of ‘Hell is other people’. The paper emphasizes the role of the author as a narrator/reteller of well-known stories and tales, both for the author as an actual person and as a literary mystification. The article demonstrates the transformation of the fairy-tale notion of ‘happiness’ into the concept of acquiring meaning as a prerequisite of the main character’s individuation.